2013
DOI: 10.1542/peds.2013-1868
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis Type 1 and Autism Spectrum Disorder

Abstract: WHAT'S KNOWN ON THIS SUBJECT: NF1 is the commonest singlegene neurodevelopmental disorder with known neurobiology and developmental impact on attention and cognition. Its impact on social functioning is described but poorly understood, with no population-based study of autism spectrum disorder (ASD) prevalence in the disorder. WHAT THIS STUDY ADDS:This epidemiological study shows high prevalence of 25% ASD in NF1 not explained by learning difficulties. ASD should be considered during clinical practice with NF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(166 citation statements)
references
References 32 publications
8
155
2
1
Order By: Relevance
“…It has long been appreciated that individuals with Neurofibromatosis type 1, caused by germline mutation of the NF1 tumor suppressor, are at high risk for intellectual and/or cognitive deficits (Costa and Silva 2003;Hyman et al 2005;Samuels et al 2009). In the past, many of these claims have remained largely anecdotal; however, recent concerted efforts have confirmed these findings (Lorenzo et al 2013;Costa et al 2014) and revealed a high incidence of ASD among NF1 individuals (Garg et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been appreciated that individuals with Neurofibromatosis type 1, caused by germline mutation of the NF1 tumor suppressor, are at high risk for intellectual and/or cognitive deficits (Costa and Silva 2003;Hyman et al 2005;Samuels et al 2009). In the past, many of these claims have remained largely anecdotal; however, recent concerted efforts have confirmed these findings (Lorenzo et al 2013;Costa et al 2014) and revealed a high incidence of ASD among NF1 individuals (Garg et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that between 30% and 70% of NF1 patients have learning disabilities (Hyman et al 2005). In addition, ;1% of children with autism spectrum disorders (ASDs) are eventually diagnosed with NF1 (Marui et al 2004), and more recent studies indicate a significant incidence of ASDs in NF1 individuals (Garg et al 2013). Genetically engineered mouse models (GEMMs) with heterozygous or conditional NF1 inactivation have behavioral phenotypes related to learning disabilities (Cui et al 2008).…”
mentioning
confidence: 99%
“…Importantly, however, NF1 is associated with impairments in several domains that overlap with ASD (including delayed social, executive, and language skills), and so the true prevalence of ASD in NF1 may be lower than these reports would indicate [24]. Nevertheless, a recent population-based epidemiologic study of children and adolescents in with NF1 using diagnostic assessment tools estimated a population ASD prevalence of 24.9% [25], well above the estimated general population prevalence of 1.5% [26].…”
Section: Psychological Comorbiditiesmentioning
confidence: 98%
“…A prevalence of 25% comorbid ASD in NF1 was established in a recent epidemiological study (Garg et al 2013). Cerebellar hypoplasia in NF1 appears to have been underestimated (Toelle et al 2015) and another study showed a strong association between gait width and spatial working memory (Champion et al 2014).…”
Section: Neurofibromatosismentioning
confidence: 96%